Two-sided market power in firm-to-firm trade - Vanessa Alviarez; Michele Fioretti; Ken Kikkawa; Monica Morlacco (Inter-American Development Bank (IDB), 2023)
We develop a quantitative theory of prices in firm-to-firm trade with bilateral negotiations and two-sided market power. Markups reflect oligopoly and oligopsony forces, with relative bargaining power as weight. Cost pass-through elasticities into import prices can be incomplete or complete, depending on the exporter's and importer's bargaining power and market shares. In U.S. import data, we find that U.S. importers have substantial market power and disproportionate leverage in price negotiations. The estimated model produces accurate predictions of the impact of Trump tariffs on pair-level prices. At the aggregate level, ignoring two-sided market power could exaggerate tariff pass-through by about 60 percent.
Keywords: F12; F13; F14; F62; 330; Market power; Global value chains; Pass-through; International trade